Football Skills of Students of Syekh Yusuf Gowa Football School Reviewed from Cardiovascular Endurance - Awaluddin, Awaluddin (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aims to determine the Football Skills of Syekh Yusuf Gowa Football School Students Reviewed from Cardiovascular Endurance. This type of research is a descriptive research type. The population in this study were all Syekh Yusuf Gowa Football athletes with a research sample of 20 people aged 13-15 years. The sampling technique was by using "random sampling". Data analysis in this study was in the form of quantitative descriptive analysis. So all statistical data used generally use statistical analysis with the help of a computer in the SPSS Version 22.00 program. Based on the test results that have been obtained, it can be concluded that the level of football skills of Syekh Yusuf Gowa Football School students reviewed from cardiovascular endurance is in the category of "Medium